Chemical constituents and biological activities of Syzygium filiforme var. filiforme stem bark / Mohd Hafiz Ahmad - Ahmad, Mohd Hafiz (2015)
The stem bark of Syzygium filiforme var. filiforme from family of Myrtaceae was investigated for its chemical constituents and biological activities. About 3 kg of the stem bark was extracted successively using solvent of different polarity. Various chromatographic methods were used to isolate and purify compounds from dichloromethane and methanol extracts such as vacuum liquid chromatography, glass column, centrifugal thin layer chromatography, thin layer chromatography and preparative thin layer chromatography…